Migration of Ethylene Vinyl Alcohol Co-Polymer in the Urinary Tract Successfully Managed - Anna Maria Ierardi; Filippo Pesapane; Antonio Arrichiello; Federico Fontana; Filippo Piacentino; Gianpaolo Carrafiello (Medicina, 2019)
Selective embolization is the treatment of choice for traumatic renal pseudoaneurysm. The use of ethylene vinyl alcohol copolymer (EVOH) was recently described as an embolic agent in peripheral lesions. The aim of a good embolic agent is to: achieve rapid and effective embolization; reach and fill distal vasculature targeted for embolization; be easy to prepare and use. Moreover, it should be highly radiopaque, controllable during administration, biocompatible and cost-effective. EVOH is a non-adhesive embolic agent and its efficacy is independent from the coagulant status. The risk of non-targeted embolization should be reduced by the good radio-opacity of the embolic material that is injected under continuous fluoroscopy. Nevertheless, symptomatic EVOH migration was described. We report a unique case of embolization of a renal pseudoaneurysm and migration of EVOH in the urinary tract. Retrograde trans-urethral removal of the migrated embolic agent was successfully performed. Our case report indicates that EVOH may not be appropriate when a fistula with renal calyx is suspected, even if its migration in the urinary tract may be managed.